Sovereign ratings and finance ministers’ characteristics - Afonso, António (2019)
This paper empirically assesses the effect of a newly-compiled set of finance ministers´ characteristics on the setting by rating agencies of the long-term sovereign rating notations. Using a sample of 26 EU countries between 1980-2012, we find that the existence of more focused delegation-oriented fiscal framework, the Minister of Finance being a woman, and the Minister of Finance having a degree in the areas of finance or “hard sciences” seems to contribute to a better sovereign rating notation, and the opposite in the case of a Law background.